Isolation and Quantification of Antidiabetic and Antioxidant Components from Saturated Fraction of Marrubium vulgare. L Leaves: Life Sciences-Phytochemistry - Ahmad Dar, Shabir; Kumar, Parveen; Gupta, Prasoon; Madishetti, Sreedhar; Sharma, Manik; Kumar, Amit (International Journal of Life Science and Pharma Research, 2021)
Marrubium vulgare L. (Lamiaceae), aerial parts has been traditionally used to cure a variety of diseases including diabetes. A good class of secondary metabolites is present in the herb; however, the potential antidiabetic agent consistently stays a secret.. The present study aimed to identify the antidiabetic agents present in M. vulgare leaf extract. The isolation of compounds from the saturated fraction was done by column chromatography and their structures were elucidated using NMR, HRMS and MS spectroscopic methods. . The antidiabetic profiling of Methonoloc Extract (MeOH) extract (500 mg/kg b.w) and its chloroform fraction (250 mg/kg b.w) was investigated in STZ- induced diabetic rats. Four bioactive compounds namely marrubiin (MV-17), marrubinone B (MV-27), ladanein (MV-19) and apigenin 7-O-β-D-(6''- p- coumaroyl) glucoside (MV-25), were isolated from chloroform fraction, oleic acid(MV-20) and Palmitic acid (MV-21) from hexane fraction of M. vulgare leaf. Among these known compounds we first time report oleic and palmitic acid in M. vulgare. Both MeOH extract (500 mg/kg b.w) and its CHCl3 fraction (250 mg/kg b.w) significantly (pË‚0.001) lowered the blood glucose level. Quantitative estimation by HPLC showed the highest concentration of MV-17, MV-20 and MV-27 in the CHCl3 fraction. Moreover this fraction also showed significant antioxidant potential measured by DPPH assay. These results confirmed that the hypoglycemic potential of chloroform fraction (IIIM-2) may be largely due to compounds MV-17, 27 and 20.